Psychological distress due to COVID-19 in parents and children’s emotional and conduct problems: the mediation role of couple adjustment and parenting stress - Cimino, Silvia; Marzilli, Eleonora; Tambelli, Renata (Psychology Hub, 2021)
The COVID-19 pandemic and its related restrictions have caused a great impact on the global economy and mental health, with short- and long-term effects on parents’ and children’s well-being. International research has reported that the psychopathological impact of COVID-19 on parents may lead to higher levels of children’s emotional-behavioral symptoms. An increase in parenting stress and a worse quality of couple adjustment has also been reported. However, no study has yet explored the possible complex interplay between the psychological impact of COVID-19 on parents, couple adjustment, parenting stress, and children’s emotional-behavioral problems. During the second wave of COVID-19, we recruited N=126 parents (56.6% mothers) with school-aged children aged 5-11 years (M=7.68; SD=2.14) via an online survey. We assessed psychological distress due to COVID-19 in parents, parenting stress, dyadic adjustment, and children’s emotional-behavioral functioning through self-report and report-form instruments. Results showed significant associations between parents’ psychological distress both with parenting stress, dyadic adjustment, and children’s emotional and conduct problems. Moreover, dyadic adjustment and parenting stress serial mediated the relationship between psychological distress due to COVID-19 and children’s emotional and conduct problems. These findings have important clinical implications on the planning of prevention programs aimed at promoting children’s well-being in the family.